EMPLOYING LOCAL WISDOM BASED SHORT STORIES FOR TEACHING ENGLISH AT ELEMENTARY SCHOOL - Hima, Aninda Nidhommil; Gusdian, Rosalin Ismayoeng (LET: Linguistics, Literature and English Teaching Journal, 2018)
In the Indonesian educational system, The English as a foreign language has an important position (Fristiara, 2017). It a affects the number of people learning English that increases every year, beginning at younger and younger ages (Rokhayani, 2017). However, the process of teaching English in elementary schools becomes problematic today. According to the situation analysis, it was found that many elementary school teachers lack of ability and knowledge in teaching EYL especially in preparing the materials. In regard to the issue, this community service project was designed to upgrade the teachers ability in designing English short stories book as their teaching material as well as teaching the stories in the classrooms. In addition, the teachers were also expected to be able to include local wisdom in their short stories. The project implementation falls into three phases as follows (1) collecting all short stories which contain local wisdom (2) translating the short stories, and (3) implementing the short stories in the classroom.